1998
DOI: 10.1039/a804299c
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of dialkylsubstituted polystannanes and their properties

Abstract: Poly(dibutylstannane) and poly(dioctylstannane) were obtained by electrochemical polymerization of dibutyldichlorostannane and dioctyldichlorostannane, respectively, in a one-compartment cell equipped with a platinum cathode and a silver anode, using tetrabutylammonium perchlorate and DME as the supporting electrolyte and the solvent, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 17 publications
1
79
0
Order By: Relevance
“…Note that the molar mass of polystannanes might decrease somewhat upon redissolution, [10] and accordingly a moderate difference in the degradation rate might result upon exposure of solutions containing in situ synthesized or redissolved polystannanes; see, for instance, the stability factors F in Table 4 and 5 for the degradation of poly(dibutylstannane) in CH 2 Cl 2 according to both methods, where F amounted to 0.43 and 0.57, respectively. It should be noted that poly(dialkylstannane)s exhibit a strong UV absorption band with an absorption maximum in the region of 370-410 nm, [7,9,13,14,[16][17][18][19] which presumably arises from the delocalization of s-electrons of the tin atoms along the polymer backbone. In several reports, this band was used for the analysis of the degree of degradation of polystannanes.…”
Section: Stability In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the molar mass of polystannanes might decrease somewhat upon redissolution, [10] and accordingly a moderate difference in the degradation rate might result upon exposure of solutions containing in situ synthesized or redissolved polystannanes; see, for instance, the stability factors F in Table 4 and 5 for the degradation of poly(dibutylstannane) in CH 2 Cl 2 according to both methods, where F amounted to 0.43 and 0.57, respectively. It should be noted that poly(dialkylstannane)s exhibit a strong UV absorption band with an absorption maximum in the region of 370-410 nm, [7,9,13,14,[16][17][18][19] which presumably arises from the delocalization of s-electrons of the tin atoms along the polymer backbone. In several reports, this band was used for the analysis of the degree of degradation of polystannanes.…”
Section: Stability In Solutionmentioning
confidence: 99%
“…In several reports, this band was used for the analysis of the degree of degradation of polystannanes. [7,[17][18][19] However, as polystannanes are sensitive to light, some degradation might be induced by the light employed for the UV-Vis measurements. We investigated the extent of this degradation with poly-(dibutylstannane), poly(dioctylstannane), and poly(didodecylstannane) in toluene solutions at a concentration of ca.…”
Section: Stability In Solutionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] These polymers, which typically are of the composition (-SnR 2 -) n and termed polystannanes, are structurally related to corresponding polymers with the semi-metals silicon or germanium (i.e., elements that are located in the periodic table in the same group as tin) and are of potential interest as semiconductors. [11][12][13] However, the synthesis of linear polystannanes in high yield and free of cyclic oligomers has been achieved only recently [2,3] and, therefore, until now the properties of polystannanes have been relatively little explored.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical reduction of diorganotin dihalides is expected to be the most important approach for the large-scale preparation of polystannanes 22. However, so far only (n-Bu 2 Sn) n and (n-Oct 2 Sn) n were prepared by electrochemical synthesis 95 (Table 5, Scheme 15). The reactions were carried out in 1,2-dimethoxyethane (DME) as solvent and with tetrabutylammonium perchlorate as supporting electrolyte.…”
Section: Polystannanesmentioning
confidence: 99%
“…In air, solid samples decompose very slowly and poly(diaryl)stannanes are air-stable over at least several weeks in the dark. No decomposition of H(n-Bu 2 Sn) n H in pentane took place, even when oxygen was bubbled through its solution 95 . It was concluded that polystannanes are stable towards oxygen but extremely reactive to moisture.…”
Section: Polystannanesmentioning
confidence: 99%